The age of three Middle Palaeolithic sites: Single-grain optically stimulated luminescence chronologies for Pech de l'Azé I, II and IV in France. Issue 95 (June 2016) - Jacobs, Zenobia; Jankowski, Nathan R.; Dibble, Harold L.; Goldberg, Paul; McPherron, Shannon J.P.; Sandgathe, Dennis; Soressi, Marie
Abstract: Optically stimulated luminescence (OSL) measurements were made on individual, sand-sized grains of quartz from Middle Palaeolithic deposits at three sites (Pech de l'Azé I, II and IV) located close to one another in the Dordogne region of southwest France. We were able to calculate OSL ages for 69 samples collected from these three sites. These ages reveal periods of occupation between about 180 and 50 thousand years ago. Our single-grain OSL chronologies largely support previous age estimates obtained by thermoluminescence dating of burnt flints at Pech IV, electron spin resonance dating of tooth enamel at Pech I, II and IV and radiocarbon dating of bone at Pech I and IV, but provide a more complete picture due to the ubiquitous presence of sand-sized quartz grains used in OSL dating. These complete chronologies for the three sites have allowed us to compare the single-grain ages for similar lithic assemblages among the three sites, to test the correlations among them previously proposed by Bordes in the 1970s, and to construct our own correlative chronological framework for the three sites. This shows that similar lithic assemblages occur at around the same time, and that where a lithic assemblage is unique to one or found at two of the Pech sites, there are no deposits of chronologically equivalent age at the other Pech site(s). We interpret this to mean that, at least for these Pech de l'Azé sites, the Mousterian variants show temporal ordering. Whether or not this conclusion applies to the wider region and beyond, the hypothesis that Mousterian industrial variation is temporally ordered cannot be refuted at this time.